2016
DOI: 10.1002/aur.1690
|View full text |Cite
|
Sign up to set email alerts
|

Severity of ASD symptoms and their correlation with the presence of copy number variations and exposure to first trimester ultrasound

Abstract: Scientific Abstract Current research suggests that incidence and heterogeneity of autism spectrum disorder (ASD) symptoms may arise through a variety of exogenous and/or endogenous factors. While subject to routine clinical practice and generally considered safe, there exists speculation, though no human data, that diagnostic ultrasound may also contribute to ASD severity, supported by experimental evidence that exposure to ultrasound early in gestation could perturb brain development and alter behavior. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 137 publications
4
29
0
1
Order By: Relevance
“…No interactions were observed for other air pollutants, even those that demonstrated main effects; ozone tends to be negatively correlated with the other pollutants examined. While earlier work has demonstrated interactions between the presence of a pathogenic CNV and an environmental exposure [Webb et al, 2016], these findings appear to be the first indication that global copy number variation may increase susceptibility to certain environmental factors, and underscore the need to consider both genomics and environmental exposures as well as the mechanisms by which each may amplify the risks for autism associated with the other.…”
mentioning
confidence: 71%
“…No interactions were observed for other air pollutants, even those that demonstrated main effects; ozone tends to be negatively correlated with the other pollutants examined. While earlier work has demonstrated interactions between the presence of a pathogenic CNV and an environmental exposure [Webb et al, 2016], these findings appear to be the first indication that global copy number variation may increase susceptibility to certain environmental factors, and underscore the need to consider both genomics and environmental exposures as well as the mechanisms by which each may amplify the risks for autism associated with the other.…”
mentioning
confidence: 71%
“…In July 2016, Webb et al 73 retrospectively analyzed a modification of Casanova's hypothesis by analyzing a possible association between ASD severity and PUS exposure within the first trimester of pregnancy with fetuses genetically predisposed to ASD. Genetic predisposition was determined, based on the presence or absence of ASD-associated copy number variations (CNVs) with structural duplications or deletions of deoxyribonucleic acid (DNA) base pairs in the genome sequence.…”
Section: Prenatal Ultrasonography and Asdmentioning
confidence: 99%
“…A recent study 1 has suggested that heterogeneity of autism spectrum disorder (ASD) may, in part, result from exposure to early ultrasound in genetically vulnerable children.…”
mentioning
confidence: 99%
“…Just over 60% recalled having at least one ultrasound in the first trimester and in those children there was a statistically significant increase in one metric of parent-reported repetitive behaviours compared to unexposed children, but no difference, or one improvement, in nine other metrics of cognitive ability, social affective behaviours or repetitive behaviours. 1 There were 133 children (7.6% of the initial cohort) with ASD-associated copy number variants. In those exposed to first trimester ultrasound there was a statistically significant decrease in non-verbal IQ and, in boys only, an increase in one metric of repetitive behaviour compared to unexposed children, but no difference on the other eight metrics.…”
mentioning
confidence: 99%
See 1 more Smart Citation